Poverty Reduction and Growth Trust?2017 Borrowing Agreements with the National Bank Of Belgium and the Swiss National Bank. (Policy Papers; Policy Paper ;, 2017)
The Fund, as Trustee of the Poverty Reduction and Growth Trust (PRGT or Trust), has entered into new borrowing agreements with the National Bank of Belgium (Belgium) and the Swiss National Bank (Switzerland), effective on August 30, 2017. These new borrowing agreements with Belgium and Switzerland provide new resources equivalent to SDR 350 million and SDR 500 million, respectively, for a total amount equivalent to SDR 850 million in new PRGT lending resources.